A Research Study on the Effect of eLearning Platforms on Employee: Employee Participation, Job Satisfaction, Employee Commitment and Employee Productivity in UAE - ALHANAEE, AWAD JUMA (2023)
Purpose The main objective of this paper is to investigate the effect of eLearning over employee engagement, job satisfaction, employee commitment and employee productivity in medium and large firms in UAE. This study's proposed questionnaire underwent pilot tests to ensure the questionnaire's validity, terms, relevance, and suitability for the target group. A final sample of 97 participants was studied after excluding cases with unsuitable responses. Results prove a significant positive relationship between eLearning and job satisfaction, employee engagement, employee commitment and employee productivity. Therefore, it is quantitatively and theoretically proven that eLearning has a positive effect on above mentioned dependent variables. Using correlation and regression analysis via SPSS to understand the relationship between independent and dependent variables. The results have been validated using Cronbach Alpha and existing literature review. The information obtained from this paper will help organizations obtain the best eLearning practices and employ the best eLearning platform and module for their employees. Also, it would add additional value to existing literature and close the current gaps related to eLearning and how it would affect professional development. Design/methodology/approach/Findings This paper aims to examine possible relationship between eLearning and employee participation, job satisfaction, employee commitment and employee productivity in medium and large size firms throughout qualitative research (a survey) using statistical analyzing method SPSS. The findings of the research prove a positive relationship between eLearning and employee participation, job satisfaction, employee commitment and employee productivity, where implementing eLearning programs at workplace increases employee participation, job satisfaction, employee commitment and employee productivity. The information obtained from survey can be used to improve the quality of existing eLearning modules or to prove the importance of eLearning and its effect on professional development. Research limitations/ implication Since employee requires continual learning and improvement in a variety of areas, this research will aid in understanding how an eLearning platform would affect employees in general organizations. Additionally, management and other stakeholders would benefit from an understanding of current practices and how it would benefit their staff members professionally. Originality/ value There is a non - availability of research in this area, particularly in the United Arab Emirates, according to a review of various literature on eLearning platforms and employee engagement, job satisfaction, employee commitment, and employee productivity. Understanding current practices and how it would help their staff members professionally will benefit management and other stakeholders in UAE. Keywords: eLearning, Employee Engagement, Job satisfaction, Job Commitment, Employee performance, United Arab Emirates